Islam and its role in global inter-religious dependence - Ashimi, Tijani Ahmad (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
Islam is actually a religion of peace, tolerance and universal brotherhood;it is embodiment of the code of life which God the Creator and the Lord of the universe has revealed for the guidance of mankind. It is a unique religion in that it has related itself to most of the religions of the world (with particular reference to Jud aism and Christianity), it does not deny truth to other religions,but says that later followers adulterated that truth by their own inventions, and that was a reason why God sent Prophet Muhammad (peace be upon him) to purify God’s religion. In fact, down the history, Islam’s relation to other religions has been ideational. i.e linking the worldview of Islam, its view of God, of reality, of man of the world and history to the other religions. It is also practical. i.e. providing a modus vivendi for Muslims and adherent of other religions to live and work together, but each group according to the values and precepts of its own faith. Thus, this humble research will apply historical and Quranic approaches (with particular reference to energetic Muslim Scholar Ismail Raji Al-Faruqi) to demonstrate homogenous nature of Islam and its tolerance toward other religions, especially, the respect that Islam gives to both Christianity and Judaism as part of Abrahamic faith .